2023
DOI: 10.3390/ijms241210395
|View full text |Cite
|
Sign up to set email alerts
|

BSR1, a Rice Receptor-like Cytoplasmic Kinase, Positively Regulates Defense Responses to Herbivory

Abstract: Crops experience herbivory by arthropods and microbial infections. In the interaction between plants and chewing herbivores, lepidopteran larval oral secretions (OS) and plant-derived damage-associated molecular patterns (DAMPs) trigger plant defense responses. However, the mechanisms underlying anti-herbivore defense, especially in monocots, have not been elucidated. The receptor-like cytoplasmic kinase Broad-Spectrum Resistance 1 (BSR1) of Oryza sativa L. (rice) mediates cytoplasmic defense signaling in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…We have previously reported that BSR1 is involved in chitin-, peptidoglycan-, and lipopolysaccharide-triggered ROS production and defense responses and ROS production is enhanced in BSR1 -OX rice [ 14 , 16 ]. Furthermore, it has been reported that BSR1 is involved in plant responses to OsPeps and damage-associated molecular patterns (DAMPs), and these responses are enhanced in BSR1 -OX rice [ 17 ]. Thus, the browning observed at the pathogen infection may be caused by cell death due to excessive ROS production by the recognition of microbe-associated molecular patterns (MAMPs) or DAMPs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously reported that BSR1 is involved in chitin-, peptidoglycan-, and lipopolysaccharide-triggered ROS production and defense responses and ROS production is enhanced in BSR1 -OX rice [ 14 , 16 ]. Furthermore, it has been reported that BSR1 is involved in plant responses to OsPeps and damage-associated molecular patterns (DAMPs), and these responses are enhanced in BSR1 -OX rice [ 17 ]. Thus, the browning observed at the pathogen infection may be caused by cell death due to excessive ROS production by the recognition of microbe-associated molecular patterns (MAMPs) or DAMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, P OsUbi7 - BSR1 rice was also reported to confer resistance to the chewing herbivore Mythimna loreyi Duponchel (Lepodoptera: Noctuidae), a rice pest [ 17 ]. As described above, by optimizing the expression level of BSR1 using a suitable promoter such as OsUbi7 , we were able to generate rice plants with BSR to four major diseases and one pest while minimizing the adverse effects of overexpression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite lacking an extracellular or transmembrane domain, RLCKs possess a serine and threonine protein kinase intracellular domain. This domain consists of 11 kinase subdomains (I to XI), which are highly preserved, in addition to a small C-end region and a brief N-end region [59,60]. The serine and threonine (Ser/Thr) motifs of the intracellular domain of RLCK proteins have been shown to be essential in interacting with these receptors [40].…”
Section: Receptor-like Cytoplasmic Kinase (Rlck) Serving As a Signal ...mentioning
confidence: 99%